PELAKSANAAN PENGABDIAN MASYARAKAT MELALUI WEBINAR NASIONAL PENELITIAN STUDI KASUS DAN PUBLIKASINYA PADA JURNAL ILMIAH - Suhardi, Muhamad (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity in the form of a National Webinar titled "Case Study Research and Its Publication in National Scientific Journals" was successfully held online on Wednesday, April 30, 2025, at 7:00 PM WIB. This initiative represents a tangible embodiment of the Tri Dharma of Higher Education in disseminating knowledge and enhancing human resource capacity in the field of research. The primary objective of the webinar was to deepen the understanding and improve the competence of lecturers and students, as the main target audience, in comprehensive case study research methodology and effective strategies for scientific publication in national journals. The implementation of the webinar involved a series of well-planned preparatory stages. The core material of the webinar detailed the benefits of case studies in education, encompassing their roles as evaluation material, in-depth investigation instruments, and complex problem-solving tools. Various types of case study research, ranging from event case studies to micro-ethnographic case studies, were also explained, providing participants with diverse methodological perspectives. The importance of research ethics and the process of scientific publication in accredited journals were also emphasized, equipping participants with practical guidance for producing high-quality scientific works. The interactive question-and-answer session demonstrated high participant enthusiasm and the success of the speaker in bridging practical questions. The results of this activity significantly increased participants' understanding of case study research and its publication strategies, aligning with the mission of community service in supporting academic capacity building and positive contributions to development. ABSTRAK Kegiatan pengabdian masyarakat berupa Webinar Nasional "Penelitian Studi Kasus dan Publikasinya pada Jurnal Ilmiah Nasional" telah sukses diselenggarakan secara daring pada hari Rabu, 30 April 2025, pukul 19.00 WIB. Inisiatif ini merupakan wujud nyata dari Tri Dharma Perguruan Tinggi dalam menyebarluaskan ilmu pengetahuan dan meningkatkan kapasitas sumber daya manusia di bidang riset. Tujuan utama webinar adalah untuk memperdalam pemahaman dan meningkatkan kompetensi dosen serta mahasiswa, sebagai target audiens utama, dalam metodologi penelitian studi kasus yang komprehensif serta strategi efektif untuk publikasi ilmiah di jurnal nasional. Pelaksanaan webinar melibatkan serangkaian tahapan persiapan yang terencana. Materi inti webinar memaparkan secara rinci tentang manfaat studi kasus dalam bidang pendidikan, meliputi perannya sebagai bahan evaluasi, instrumen penyelidikan mendalam, dan alat pemecahan masalah kompleks. Berbagai jenis penelitian studi kasus, mulai dari studi kasus peristiwa hingga studi kasus mikro etnografi, turut dijelaskan, memberikan perspektif metodologis yang beragam kepada peserta. Pentingnya etika penelitian dan proses publikasi ilmiah di jurnal terakreditasi juga ditekankan, membekali peserta dengan panduan praktis untuk menghasilkan karya ilmiah berkualitas. Sesi tanya jawab yang interaktif menunjukkan antusiasme tinggi peserta dan keberhasilan narasumber dalam menjembatani pertanyaan-pertanyaan praktis. Hasil kegiatan ini secara signifikan meningkatkan pemahaman peserta mengenai penelitian studi kasus dan strategi publikasinya, selaras dengan misi pengabdian masyarakat dalam mendukung pengembangan kapasitas akademik dan kontribusi positif terhadap pembangunan.